CONSUMER PURCHASE INTENTION TOWARD INSTANT NOODLES - Aiman bin Mohammed; Wan Rusni binti Wan Ismail; Norliana binti Hashim; Nor Hafizah binti Mazlan (International Journal of Accounting, Finance and Business, 2022)
The purpose of this study was to identify the relationship between the factors of convenience (CO), product attributes (PA), subjective norms (SN) and perceived risk (PR) toward consumer purchase intention toward instant noodles. The population in this study was consumers who have experience purchasing and consuming instant noodles in Malaysia. 465 respondents were gathered, and the collected data were analyzed using SPSS. The relationship between the factors of convenience (CO), product attributes (PA), subjective norms (SN) and perceived risk (PR) toward consumer purchase intention toward instant noodles has been analyzed by using Spearman's Rho correlation as the data was not normally distributed. The findings show that convenience, product attributes, and subjective norms have a significant relationship between consumers' purchase intention toward instant noodles. Nevertheless, consumer perceived risk towards instant noodles recorded an insignificant relationship with purchase intention.